Development of an Integrated thermal hydrolysis process - Anaerobic Digestion (THPAD) Model - Olando, Alexander (Department of Civil Engineering, 2023)
Historically, anaerobic digestion is one of the most common processes used to treat sludge generated from wastewater treatment plant (WWTP) processes. However, with the exponential increase in populations, which implies an increase in WWTP loads, the amount of waste generated poses an imminent problem to the handling capacity of current anaerobic digesters. Subsequently, there has been a lot of research into various physical and chemical processes that would allow for a more efficient sludge handling mechanism. Studies have reported various advantages associated with digesting sludge at higher temperatures known as thermophilic temperatures. These advantages include increased sludge handling capacity, a higher degree of sludge biodegradability and subsequently increased methane production and better sludge dewatering characteristics implying cheaper sludge transportation costs just to mention a few. However, despite the advantages associated with thermal treatment, this technology has not yet been proven in a South African context. This project involved the development of an integrated thermal hydrolysis process (THP) and anaerobic digestion (AD) model capable of simulating these processes at elevated temperatures. A comparative desktop case study of the existing AD facility at the Cape Flats wastewater treatment works (CFWWTW) in Western Cape, South Africa was investigated following the City of Cape Town's (CCT) initiative to retrofit a THP unit to the anaerobic digesters to help deal with the increase in sludge handling capacity. A comparison was therefore carried out, investigating the base case scenario of maintaining the existing conventional mesophilic anaerobic digesters (MAD) and retrofitting a THP unit to the conventional anaerobic digesters (THPAD). A steady-state THP and AD model was developed and used in conjunction with an integrated dynamic THP and modified AD (termed as the Extended-UCTSDM3P) model for simulating both the conventional MAD and THPAD processes. This allowed for a comparison of results not only between the two processes, but also the two types of models. These models were then used to simulate the treatment of a mixture of primary sludge (PS) and waste activated sludge (WAS) at a ratio of 60:40 with the WAS obtained from a Nitrification Denitrification Biological Excess Phosphorus Removal (NDBEPR) activated sludge treatment. The AD models, therefore, accounted for the increased phosphorus concentration as a result of iv polyphosphates (PP) breakdown and consequently the possible precipitation of struvite (MgNH4PO4) from the AD liquor. The results showed that the THPAD configuration allowed the digesters to process 2.3 times more sludge than with the conventional mesophilic anaerobic digesters. Furthermore, the methane production in the THPAD was conservatively calculated to be 2.5 times higher than the MAD. This implied an increased potential for use of the methane gas as an alternative source of energy in the wastewater treatment plants. Given that no laboratory experiments were carried out, the results were based on theoretical scenarios and knowledge collected from an extensive literature review. However, given the capacity, flexibility and detail the model has been developed to, different scenarios in the anaerobic digestion process can be investigated and valuable practical insight extracted. Furthermore, through calibration with accurate meaningful data from a pilot or full-scale plant, the developed model is a tool that could be used in predicting digester performance.